Towards the 'secondary worlds' in Henze's opera Elegy for Young Lovers (Orfeu, 2020)
This article attempts to trace the dramatic-musical origins of the opera in three acts Elegy for Young Lovers (1961), with music by the German composer Hans Werner Henze and libretto by Auden and Kallman. By researching literary and theoretical sources on this work, with emphasis on the authors’ own writings, it was examined the extrinsic resources that contributed to the constitution of the internal dramatic structure. These resources are, on the one hand, cultural influences that interacted in the construction of the artistic identity of the work and, on the other hand, conventions borrowed from other traditions, such as the topics of the lyrical repertoire, the concepts of primary and secondary worlds of fiction literature, and possible references to known personalities, which served as inspiration for the characterization of certain roles. It was found that extrinsic resources, besides contributing to the dramatization processes in opera, also play an important role in the elaboration of an underlying didactic discourse.